Modelling of critical infrastructure interdependencies for vulnerability analysis - Lin, Jiwei (2018)
Critical infrastructures are systems required for producing and distributing essential goods and services needed for the proper functioning of a city or state. These infrastructures function in collaboration with one another, forming an interconnected networked structure with resulting interdependencies that make them potentially vulnerable to significant impact and disruption due to physical or other forms of hazards. This thesis describe a critical infrastructure interdependency model that analyses the interdependencies accordingly, based on a Leontief input-output model that is generalizable to almost all forms of critical infrastructure systems. To demonstrate its applications, two case studies (Singapore Pulau Bukom refinery fire in 2011 and Japan Tohoku earthquake in 2011) are presented to demonstrate how the model can be used to compute how the disruption/impact in one infrastructure sector cascades to other sectors. Next, the critical infrastructure interdependency model is extended to accommodate features of a physical critical infrastructure, such as their topological network structure, so as to enhance the model’s applicability to real world disruptive scenarios, such as a terrorist attack on one or more entities within the network. Scenarios involving a single physical infrastructure network as well as two physical infrastructure networks have been analysed and implemented in a software environment to simulate various possible scenarios of a disruptive event and provide the overall impact in terms of economic losses. Finally, the model is used for all types of critical infrastructures at a national scale to analyse worst case scenarios possible if an area of a specified size is being disrupted by some hazard (e.g. a dirty bomb). The developed model helps to provide a better understanding of the severity and extent of the disruptive scenarios and serves as a quick and cost effective decision deployment tool for use by relevant stakeholders.